Music and dance as an alternative form for the emotional, psychological and physical restoration of children and youth with addiction problems people deprived of liberty - Álvarez Mora, Marcela (University Magazine, 2022)
Due to how serious and delicate it is to have young people involved in drug or alcohol addictions, with few limits in their homes, no structure, meal times, study or a routine, to try to find an assertive solution for them, there are rehabilitation centers that They offer various possibilities for recovery. It also has a whole structure, which Many times young people, due to lack of habit, do not tolerate it and look for the possibility of escaping and abandon their rehabilitation treatment. In restoration centers, the aim is to achieve a harmony within the recovering population, through music and movement; as both make it possible to provide well-being and relevant therapeutic tools to treat the unbalanced behaviors or psychosomatic conditions of people, in this case, youths. It should be mentioned that due to the deprivation of liberty, they tend to present behaviors aggressive against them and them and those in charge of the center. Music and the use of movement They try to repair from the inside out. Looking for balance and mental health, which It provides the practice of some artistic discipline in this case music and movement; for all healing benefits, becoming more comprehensive disciplines for their development and healing. Dalcroze (1931).